Association between dietary vitamin B6 intake and constipation: a population-based study - Liu, Xuefeng; Liu, Yuedong; Shu, Yuping; Tao, Hongwu; Sheng, Zewei; Peng, Yuyu; Cai, Meiqi; Zhang, Xiaoming; Lan, Weiru (Frontiers in Nutrition, 2024)
Background: Numerous studies have suggested a link between dietary micronutrient intake and the onset of constipation. Nevertheless, there hasn't been much research done on the potential relationship between vitamin B6 and constipation. The purpose of this study was to determine whether dietary vitamin B6 consumption and chronic constipation are related among adult participants in the National Health and Nutrition Examination Survey (NHANES). Method: The study made use of information from the 2009–2010 NHANES health and nutrition survey. Respondents' dietary information was gathered using 24-hour dietary recalls. A range of statistical techniques, including as interaction tests, subgroup analyses, and curve fitting analyses, were used to examine the connection between dietary vitamin B6 intake and chronic constipation. Result: This study included 3,643 patients, with 270 (7.41%) diagnosed with persistent constipation. A fully adjusted multiple logistic regression analysis found that increasing dietary vitamin B6 consumption (OR=0.78, 95% CI: 0.68-0.89) was linked to a lower incidence of constipation, with significance at p<0.05. After accounting for numerous factors, the odds ratio and 95% confidence interval for the third tertile compared to the reference group (first tertile) were 0.85 (0.74, 0.98), with statistical significance at p<0.05. Furthermore, subgroup analysis and interaction assessments revealed a substantial negative link between vitamin B6 intake and the occurrence of constipation, particularly in males and alcohol drinkers (all P values were less than 0.05). Conclusion: This study found an inverse connection between vitamin B6 consumption and the prevalence of persistent constipation. More extensive prospective trials are needed to fully examine the long-term influence of vitamin B6 on persistent constipation.